Prevalence and characterization of Vibrio spp. in seawater and wet-market cockles from Kuala Selangor, Malaysia, and risk of acquiring V. vulnificus infections from cockle consumption - Chang, Wei San (2018)
It has been estimated that global sea surface temperature is approximately 1ºC higher than 140 years ago and is one of the primary physical impacts of climate change. The aim of this study was to determine the prevalence of Vibrio cholerae, V. parahaemolyticus and V. vulnificus in cockle and seawater samples. The samples were collected monthly from coastal area of Kuala Selangor over a one year period. To quantify the prevalence of V. cholerae, V. parahaemolyticus and V. vulnificus in cockle and seawater samples, the most probable number (MPN) method was used in combination with the polymerase chain reaction (PCR) which was used to classify the isolates by detecting their specific genes. Following with the antibiotic resistance study by using E test to characterize V. parahaemolyticus strains isolated from the samples. The characteristics of V. parahaemolyticus were also assessed by the investigation of the levels of multiple antibiotics resistant V. parahemolyticus in cockles under the effect of different storage conditions. Furthermore, an examination of the survivability of V. parahaemolyticus during steaming of cockles was conducted. Finally, a preliminary step-wise risk assessment was carried out to estimate the risk (probability of infection leading to illness) posed by V. vulnificus from the consumption of cockles in Malaysia. The prevalence results showed that V. cholarae, V. parahaemolyticus and V. vulnificus were detected in both cockle and seawater samples. Out of the 247 total samples tested, 243(98.4%) samples were positive for V. parahemolyticus. Following with 11 (4.5%) and 23(9.3%) of V. cholarae and V. vulnificus in total samples, respectively. Pathogenic V. parahemolyticus and V. cholerae strains were only detected in cockle samples, with the prevalence of 0.4% and 5.3%, respectively. Whereas pathogenic V. vulnificus strain was detected in both cockle and seawater samples with the prevalence of 8.5%. The prevalence of V. parahaemolyticus and V. vulnificus in total samples were found positively correlated to the seawater temperature, but not with V. cholerae. The study revealed that seawater temperature influences the prevalence of these pathogens. Overall, among those V. parahaemolyticus isolates obtained from cockles (n = 22) and seawater (n = 6), the resistance proportions were highest for tetracycline (8; 28.6%). Following with 5 (17.9%) were resistant to trimethoprim-sulfamathoxazole, 3 (10.7%) were resistant to doxycycline. Also, 2 (7.1%) were resistant to cefotaxime and ceftriaxone. All V. parahaemolyticus isolates regardless the sources were susceptible to ceftazidime, gentamicin, ciprofloxacin and levofloxacin. MAR index of V. parahemolyticus isolates ranged from 0.11-0.44. Seventy percent of the isolates showed MAR index > 0.2. The majority of multiple antibiotic resistance combinations included doxycycline and tetracycline. For the investigation of the effects of handling practices in home kitchen level, specifically ambient exposure, refrigeration and icing storage on the levels of high multiple antibiotic resistant indexes V. parahaemolyticus in cockles. The results indicated that different storage conditions had a significant effect on the growth of V. parahaemolyticus. Given that most V. parahaemolyticus are associated with consumption of shellfish and cockle’s popularity in Malaysia, examination of the survivability of pathogenic V. parahaemolyticus strains in cockles upon steaming process was conducted. Based on the data obtained, Regression analysis of the survival curve showing the linear correlation between log number of pathogenic V. parahaemolyticus and the steaming time (R2= 0.88). The results indicate that steaming time of minimum eight minutes is necessary for safe consumption of cockles free of pathogenic V. parahaemolyticus. This simple step-wise risk assessment, concerning acquisition of V. vulnificus from consumption of cockles among different major ethnic groups, susceptibility populations and gender in Malaysia, has utilized data from the previous chapters and from diverse sources in an attempt to estimate risk of infection. From the obtained results, Malays were found exposed to the greater risk due to higher consumption pattern of cockles, compared to Chinese. Among susceptible populations, elderly population was found exposed to the greatest risk followed by diabetes, alcoholism and AIDS population. Likewise, male population was found exposed to the greater risk of septicaemia infections, compared to female population regardless of their binge drinking habit. Contamination of cockles and seawater with V. cholera, V. parahaemolyticus and V. vulnificus reflects the contamination of the environment from which the cockles were harvested. Consumption of contaminated cockles present with these pathogens is likely to cause infections and pose significant risks to human health. Treatment may benefit from the use of ceftazidime, ciprofloxacin, levofloxacin and gentamicin, which were among the antibiotics 100% effective against V. parahaemolyticus isolated in this study. Additionally, cockles intended for partial cooked consumption should be eaten immediately following purchase or harvest, and not left at ambient temperature. Apart from this, cockles should be cooked sufficiently before consumption to safeguard the public health.